Beyond Obligation: An Interpretative Phenomenological Study of Utang na Loob Among Female Adoptees - Jenelle De Villa; Karen Gayl Dela Cruz; Aizel Del Mundo; Faith Anne Dela Vega; Jose Antonio Miguel Dizon; Christian Tejeresas (Advanced Qualitative Research, 2026)
The qualitative study “Utang na Loob from an Adopted Child’s Perspective” explored the lived experiences of adopted children, focusing on gratitude, acceptance, and reciprocity. Semi structured interviews were conducted with five female adoptees aged 20–30 from Batangas, Philippines. Interpretative Phenomenological Analysis (IPA) was used because it is well suited to examining how individuals make meaning of deeply personal and relational experiences. Since utang na loob involves layered emotions of gratitude, reciprocity, and identity negotiation, IPA provided the lens to capture both lived realities and the interpretative processes through which adoptees understand familial bonds. Four major themes emerged: (1) Fulfillment in Social Bonds, emphasizing supportive relationships; (2) Gradual Acceptance to Deep Gratitude, reflecting identity embrace and appreciation; (3) Reciprocal Devotions, highlighting the desire to return love and support; and (4) Consistent Expression of Appreciation, underscoring acknowledgment of parental sacrifices. Existing qualitative and cultural studies on utang na loob have mainly examined biological families or broader Filipino social ties, leaving a gap in understanding its expression within adoptive families. This study addresses that gap by centering on female adoptees’ perspectives, extending the discourse beyond blood relations. The findings advance qualitative scholarship in social science and cultural psychology by reframing utang na loob as a heartfelt response rooted in love, reciprocity, and enduring gratitude rather than obligation. This shows how Filipino values adapt to diverse family structures and enrich qualitative research by revealing nuanced processes of identity formation, emotional negotiation, and relational reciprocity in adoptive contexts.